Eating patterns and meal frequency of elite Australian athletes - Burke, L. M.; Slater, G.; Broad, E. M.; Haukka, J.; Modulon, S.; Hopkins, W. G. (International Journal of Sport Nutrition and Exercise Metabolism, 2003)
We undertook a dietary survey of 167 Australian Olympic team athletes (80 females and 87 males) competing in endurance sports (n = 41), team sports (n = 31), sprint- or skill-based sports (n = 67), and sports in which athletes are weight-conscious (n = 28). Analysis of their 7-day food diaries provided mean energy intakes, nutrient intakes, and eating patterns. Higher energy intakes relative to body mass were reported by male athletes compared with females, and by endurance athletes compared with other athletes. Endurance athletes reported substantially higher intakes of carbohydrate (CHO) than other athletes, and were among the athletes most likely to consume CHO during and after training sessions. Athletes undertaking weight-conscious sports reported relatively low energy intakes and were least likely to consume CHO during a training session or in the first hour of recovery. On average, athletes reported eating on ~5 separate occasions each day, with a moderate relationship between the number of daily eating occasions and total energy intake. Snacks, defined as food or drink consumed between main meals, provided 23% of daily energy intake and were chosen from sources higher in CHO and lower in fat and protein than foods chosen at meals. The dietary behaviors of these elite athletes were generally consistent with guidelines for sports nutrition, but intakes during and after training sessions were often sub-optimal. Although it is of interest to study the periodicity of fluid and food intake by athletes, it is difficult to compare across studies due to a lack of standardized terminology.